Characteristics of Boleng Strait Sediments, East Nusa Tenggara, and its Relationship with Current Velocity - Hananto Kurnio; Ai Yuningsih; Rina Zuraida (BULLETIN OF THE MARINE GEOLOGY, 2018)
Islands of Nusa Tenggara are separated by narrow and deep straits resulted from complex tectonic activties. One of the strait is Boleng Strait where tidal current as high as 310 cm/s occurred which might be suitable for an ocean current power plant. Utilization of such resources would need various information of the area, one of them is sediment textures that characterized the seafloor and coastal area and their relationship to current velocity. Grain size analyses were conducted on 12 seafloor sediment samples and 26 coastal sediment samples to identify sediment texture. An additonal 14 seafloor sediment samples with limited volume were observed to determine their sediment types. The result of analysis yielded six types of seafloor sediments: Sand, Gravelly Sand, Sandy Gravel, Silty Sand and Sandy Silt. The sediment grain size is equally influenced by current velocity (r = 0.57) and water depth (r = 0.52) which is reflected by sediment distribution: coarse–grain sediments cover the area near Boleng Strait which has stronger current and fine–grain sediments cover the inner part of the Lewoleba Bay. Plot of six sets of mean grain size and current velocity on Hjulström diagram shows that most of seafloor sediments are on the move and one (SBL. 14) is being eroded. This condition might affect the turbine and thus needs to be taken into consideration when designing the turbine. Grain size analyses on coastal sediment samples show that the mean grain size of coastal sediments ranges between 0.19 mm and 0.62 mm with average value of 0.33 mm that is classified as medium sand. Sand fraction in coastal sediments composes 57% to 100% of the sediments. Observation on mineralogy of the sediments shows abundance of magnetite that concentrates in the fine and medium sand fractions. The presence of magnetite indicate that current–related selective entrainment occurs in the study area. This condition suggests that the coastal area is also strongly affected by ocean current.Key words: current velocity, sediment grain size, Boleng Strait.Aktivitas tektonik di Nusa Tenggara Timur menyebabkan terbentuknya batimetri yang kompleks di sekitar kepulauan tersebut yang dicirikan oleh adanya selat sempit dan dalam yang memisahkan pulau–pulau. Salah satu selat tersebut adalah Selat Boleng yang memiliki kecepatan arus terukur maksimum sebesar 310 cm/s yang dapat digunakan sebagai pembangkit energi listrik. Desain turbin arus akan membutuhkan banyak informasi, salah satunya adalah sedimen dasar laut dan pantai serta hubungannya dengan kecepatan arus. Analisis besar butir dilakukan pada 12 sampel sedimen dasar laut dan 26 sampel sedime pantai untuk menentukan jenis sediment. Sebanyak 14 sampel sedimen dasar laut dengan volume terbatas diamati untuk mengetahui jenis sedimen. Hasil analisis menunjukkan bahwa sedimen dasar laut terdiri atas enam jenis: Pasir, Pasir Kerikilan, Kerikil pasiran, Pasir Lanauan dan Lanau Pasiran. Ukuran butir sedimen dipengaruhi oleh kecepatan arus (r = 0.57) dan kedalaman laut (r = 0.52) yang tercermin pada distribusi sedimen: sedimen berukuran kasar menutupi dasar laut di dekat Selat Boleng yang berarus lebih kuat, dan sedimen berukuran halus menutupi dasar laut di bagian dalam Teluk Lewoleba. Plot enam set ukuran butir rata–rata dan kecepatan arus pada diagram Hjulström menunjukkan bahwa hampir seluruh sampel berada dalam kondisi bergerak dan bahkan satu (SBL. 14) sedang mengalami erosi. Kondisi ini akan mempengaruhi turbin sehingga perlu dijadikan pertimbangan saat mendesain turbin. Hasil analisis besar butir pada sedimen pantai menunjukkan bahwa ukuran butir rata–rata sedimen pantau berkisar 0.19 mm dan 0.62 mm dengan nilai rata–rata 0.33 mm yang termasuk dalam fraksi pasir sedang. Fraksi pasir dalam sedimen pantai menyusun 57%–100% sedimen. Pengamatan mineralogi menunjukkan melimpahnya magnetit yang terkonsentrasi pada fraksi pasir halus–sedang. Keberadaan magnetit menunjukkan adanya proses pemisahan yang berkaitan dengan arus laut. Kondisi ini menunjukkan bahwa daerah pantai Selat Boleng juga dipengaruhi oleh arus laut. Kata Kunci: kecepatan arus, ukuran butir sedimen, Selat Boleng.